Phase-Out of Leaded Gasoline in Oil Importing Countries of Sub-Saharan Africa : The Case of Tanzania - Bultynck, Patrick (World Bank, Washington, DC, 2014)
This is one of four documents of a series presenting the results of studies, workshops and action plans recently undertaken for four sub-Saharan African countries (Ethiopia, Mali, Mauritania and Tanzania) on the elimination of lead in gasoline. This document describes the work realized in Tanzania. These four countries have the particularity of being oil importing countries without local refining capability. The transition to unleaded gasoline should therefore theoretically be easier to implement in such a context than in oil-producing or oil-refining countries. Several technical issues (such as the definition of specifications) and regulatory issues must however be resolved in order to eliminate lead from gasoline in these countries. This is precisely the goal of the studies realized in these four oil-importing countries. These studies and workshops are financed by The Energy Sector Management Assistance Programme (ESMAP) which plays a decisive role towards the transfer of technology and knowledge in energy sector management to governments of developing countries and of economies in transition. By bringing its own resources and expertise, ESMAP strengthens the partnership of the Clean Air Initiative in sub-Saharan African Cities. This ESMAP contribution also allows for reaching the goal set during the Dakar conference of June 2001: the complete elimination of leaded gasoline in sub-Saharan Africa as soon as possible, at the latest by 2005.